A deformable tetrahedron rolling mechanism (DTRM) based on URU branch. (November 2020) - Li, Yezhuo; Wang, Zhirui; Xu, Yugong; Dai, Jian S; Zhao, Ziming; Yao, Yan-an
Highlights: A novel deformable tetrahedron rolling mechanism is proposed based on URU branch. Rolling gaits are planned to reduce the displacement error of the mobile mechanism. Trajectory of the center of mass is optimized to reduce the actuator torque. Experimental results of physical prototypes of the rolling mechanism are presented. Abstract: The purpose of this paper is to put forward a novel deformable tetrahedron rolling mechanism (DTRM). This new reconfigurable mobile mechanism with the external tetrahedral shape can be regarded as a parallel mechanism with a variable platform, that is constructed by four vertices and six edges corresponding to four platforms and six URU chains. Mechanical design is introduced, and the degree of freedom (DOF) is analyzed. Equivalent planar mechanism analysis method is proposed for the symmetrical mechanical structure to simplify the theoretical analysis process. Based on the symmetric-drive rolling locomotion, impact and non-impact rolling gait are planned, respectively corresponding to different joints workspace, to reduce the displacement error. Aiming at non-impact rolling gait, the motion strategy is established instead of moving with pre-set driving parameters, as the basis of the control system. Then a trajectory optimization of the center of mass (CM) based on actuator torque analysis is carried out to reduce the actuator torque. To verify the rolling locomotion, we present the results of a series of experiments, performed on a manufactured prototype.